Construction of Diagnostic Tests to Diagnose the Misconceptions of Junior High School Students on Dynamic Electrical Materials - Novrina Ika (Journal of Teaching and Education, 2022)
he research objectives are to 1) develop a valid and reliable diagnostic test, and 2) find out the misconceptions experienced by high school students on Dynamic Electricity by using a diagnostic test with a three-level format that has been developed. This research is a development research using the Research Development (RD) procedure of the Borg Gall model which was modified following Treagust's research flow. The stages are, 1) the stage of determining content, 2) the stage of gathering information and 3) the stage of development and validation. The research instrument was a validation sheet, and a diagnostic test sheet with three levels of multiple choice to diagnose misconceptions. Standardization of test instruments with item validation tests using biserial point coefficients, reliability tests with KR-20 and other general tests such as tests of difficulty level and differentiating power. This research was conducted in two places and two different samples. Phase 1 and phase 2 of initial product design were carried out at MA Baitul Arqom Polinggona for classes Xa, Xb and Xc as many as 59 students, and only 38 were involved in product design trials. Meanwhile, stage 3 of development and validation was carried out at SMA Neg. 5 Kendari in class XII IPA1, XII IPA2, XII IPA3, XII IPA4, and XII IPA5 as many as 189 students were tested on a large scale and analyzed their misconceptions on dynamic electricity. The research took place from April to November 2017. The results of the research that have been developed are in the form of a diagnostic test with the characteristics of the questions having a three-level format, namely answers, reasons and confidence levels. This test consists of 21 items that have been declared valid based on the validity test, with a reliability value of 0.75 (good), an average difficulty index and very good discriminating power. The results identified with this diagnostic test are the percentage of students experiencing misconceptions of 49.4%, understanding the concept of 36.6%, understanding but the concept is still weak 6.9%, not understanding the concept of 5.6% and the remaining 1.1% is the percentage of students whose answers are correct but from 100% of the guesses.